Penentuan Biaya Produksi Sagu Pada Usaha Ibu Eka Di Desa Nolloth, Kecamatan Saparua Timur, Kabupaten Maluku Tengah - Cresmenda Patty; Elisabeth Riupassa; Maxmilian Ernest Mauwa (Jurnal Administrasi Terapan, 2024)
The cost of production is an important factor in a business, because it cab help companies determine appropriate selling prices, calculate profits, monitor production expenses, and evaluate production processed for potential improvement. One of the challenges faced by individual businesses, such as ibu Eka's, is accurately calculating production costs. Not all expenses incurred during the production process are included as production costs, as only the costs of raw materials, auxiliary materials, and fuel are considered. This leads to inaccuracies in calculating the total production costs for producing sagu (sago). This study adopts a descriptive quantitative approach. The quantitative data collected includes the production costs incurred for sago production in July 2024, sourced from ibu Eka, the business owner. Data was obtained through interviews and direct observation at the research location. The collected data was analyzed using the full costing method to determine the total production cost of sagu (sago). The findings indicate that the raw material cost for sago production was IDR 403,500, direct labor costs amounted to IDR 180,000, and factory overhead costs were IDR 131,183. Consequently, the total production cost for a single batch of sago production in July 2024 was IDR 714,683. Keywords: Production Costs, Full Costing